The TERT variant rs2736100 is associated with colorectal cancer risk. - Kinnersley, B; Migliorini, G; Broderick, P; Whiffin, N; Dobbins, SE; Casey, G; Hopper, J; Sieber, O; Lipton, L; Kerr, D; Dunlop, MG; Tomlinson, I; et al. (2012)
BACKGROUND: Polymorphic variation at the 5p15.33 (TERT-CLPTM1L) locus is associated with the risk of many cancers but a relationship with colorectal cancer (CRC) risk has yet to be defined. METHODS: We used data from six genome-wide association studies (GWAS) of CRC, linkage disequilibrium mapping and imputation, to examine the relationship between 73 single-nucleotide polymorphisms at 5p15.33 and CRC risk in detail. RESULTS: rs2736100, which localises to intron 2 of TERT, provided the strongest evidence of an association with CRC (P=2.28 × 10⁻⁴). The association was also shown in an independent series of 10 047 CRC cases and 6918 controls (P=0.02). A meta-analysis of all seven studies (totalling 16 039 cases, 16 430 controls) provided increased evidence of association (P=2.49 × 10⁻⁵; per allele odds ratio=1.07). The association of rs2736100 on CRC risk was shown to be independent of 15 low-penetrance variants previously identified. CONCLUSION: The rs2736100 association demonstrates an influence of variation at 5p15.33 on CRC risk and further evidence that the 5p15.33 (TERT-CLPTM1L) locus has pleiotropic effects (reflecting generic or lineage-specific effects) on cancer risk.